Formaldehyde Exposure During Pregnancy. Issue 3 (May 2015) - Amiri, Azita; Pryor, Erica; Rice, Marti; Downs, Charles A.; Turner-Henson, Anne; Fanucchi, Michelle V.
Abstract: Background: Pregnancy is a particularly vulnerable time for exposure to indoor air pollutants, such as formaldehyde (FA), which is linked to spontaneous abortion, congenital malformations, and premature birth. Purpose: To determine personal exposure to FA during pregnancy, and to identify the relationship between FA exposure levels and potential residential sources of FA. Study Design and Methods: The study sample consisted of 140 pregnant women recruited from obstetrical clinics in Huntsville, Alabama. Formaldehyde exposure was measured by FA vapor monitor badges. Questionnaires were administered to participants to identify potential residential sources of FA. Urine cotinine, a surrogate for tobacco smoke exposure, was also used as an indicator of a possible source of residential exposure to FA. Results: The mean level of FA exposure by vapor monitor badge was 0.04 parts per million (ppm) ( SD = 0.06; range 0.003-0.54 ppm). Minimum risk levels of 0.03 and higher were found in 36.4% of participants. Exposure levels of FA were higher in spring than winter ( p < 0.001). Exposure levels of FA were correlated with indoor temperature of dwellings ( p < 0.02), installation of new carpet within last 5 years ( p < 0.04), and use of nail polish ( p < 0.01). No relationship was found between FA exposure and urine cotinine levels. Clinical Implications: Formaldehyde exposure may increase at various times in the lives of women; however, it is of particular concern during pregnancy because of perinatal risk to the exposed fetus. Abstract : Pregnancy is an especially vulnerable time for exposure to indoor air pollutants such as formaldehyde. This research evaluated formaldehyde exposure among 140 pregnant women. Average exposure level of participants exceeded recommended limits for residential dwellings. Nurses should discuss sources of formaldehyde (home remodeling, new carpet, new furniture and nail polish) with pregnant women.